2002
DOI: 10.1037/0735-7044.116.6.1022
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive deficits in docosahexaenoic acid-deficient rats.

Abstract: This study investigated the influence of brain docosahexaenoic acid (DHA) deficiency on simple and complex olfactory-based learning and memory in 2nd generation (F2) adult male rats. Rats raised and maintained on either an n-3-adequate or an n-3-deficient diet were tested for acquisition of an olfactory learning set and an olfactory memory task, and for motivation to obtain a water reward. Despite a 76% decrease in brain DHA, n-3-deficient rats were able to acquire most simple 2-odor discrimination tasks but w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
98
2
5

Year Published

2004
2004
2011
2011

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 168 publications
(112 citation statements)
references
References 43 publications
5
98
2
5
Order By: Relevance
“…Poorer performance was observed in animal studies on such tasks as the Y-maze (33), active avoidance (34), brightness discrimination (35), shock avoidance (36), spatial tasks (14,37,38), olfaction-cued discrimination (39,40), and neuromotor skills (41) when n-3-deficient diets are fed. Human infants perform more poorly on neurodevelopmental tests when given formulas without DHA relative to formulas with DHA (42)(43)(44).…”
Section: Discussionmentioning
confidence: 99%
“…Poorer performance was observed in animal studies on such tasks as the Y-maze (33), active avoidance (34), brightness discrimination (35), shock avoidance (36), spatial tasks (14,37,38), olfaction-cued discrimination (39,40), and neuromotor skills (41) when n-3-deficient diets are fed. Human infants perform more poorly on neurodevelopmental tests when given formulas without DHA relative to formulas with DHA (42)(43)(44).…”
Section: Discussionmentioning
confidence: 99%
“…However, the essentiality of fatty acids cannot be inferred from such studies. Experimental studies, where more control can be achieved, show that animals that are fed diets deficient in n-3 fatty acids exhibit neuronal deficits, including memory, sensory, and visual abnormalities (18). DHA supplementation in rodents and nonhuman primates leads to increased brain DHA concentrations and enhanced performance on a wide variety of learning, memory, and problem-solving tasks (19)(20)(21).…”
mentioning
confidence: 99%
“…This study, which showed the beneficial effect of DHA on episodic memory (avoidance learning ability) in AD model rats, also found an associated increase in DHA corticohippocampal levels and a decrease in products associated with neuronal cell death (Hashimoto et al, 2002). Additionally, relative to omega-3 adequate rats, those that were deficient in neuronal DHA were able to perform simple learning tasks but were impaired regarding performance on a more complex, higher-order learning task (Catalan et al, 2002). Crucially, the concentrations of DHA and AA have been found to be decreased in the hippocampus of older rats, as compared with younger animals, whereas enriching the diet with omega-3 fatty acids has been found to result in full restoration of DHA and partial restoration of AA (McGahon, Martin, Horrobin, & Lynch, 1999).…”
Section: Omega-3 Fatty Acidsmentioning
confidence: 87%